Multicomponent reactions as versatile tool: development of a mild approach to 1, 3-benzothiazine-2-thiones. Issue 43 (28th October 2015) - Stalling, Timo; Pauly, Jan; Kröger, Denis; Martens, Jürgen
Abstract: A convenient multicomponent reaction for the synthesis of a variety of rarely investigated 1, 3-benzothiazine-2-thiones using carbon disulfide, primary amines and ortho -halogenated benzaldehydes as commercially available substrates is reported. Additionally, the high performance of the newly developed one-pot procedure enables a direct route to a wide range of analog annulated polyheterocyclic structures. The potential of these compounds for the late-stage elaboration of high-functionalized molecules by simple synthetic operations is demonstrated in selected subsequent derivatizations giving heterocyclic products of high diversity. Graphical abstract: